A Ukrainian Interpretation of Chinese Philosophy in the Soviet Period: A Review of "Chinese Studies in Ukrainian Philosophy of the Soviet Period" - Feng-Shuo Chang (International Society of Philosophy and Cosmology, 2021)
Rudenko and Liashenko's (2020) "Chinese studies in Ukrainian philosophy of the Soviet period" explores the philosophy and political thought of that time through the study of a Soviet-era book on Chinese philosophy. Their article argues that the content and structure of Dmytrychenko and Shynkaruk's (1958) book "The development of philosophical thought in ancient China" reflects its authors' political education intentions. This analytical argument is comprehensively presented in the paper and effectively articulates the particularity of this Ukrainian book on Chinese philosophy. In this article, I examine Rudenko and Liashenko's paper from the perspective of positivism and of an individual who received a traditional Chinese education. Through a comparison with other books on Chinese philosophy, I discuss Rudenko and Liashenko's argument regarding the materialist historical view of Dmytrychenko and Shynkaruk's book. The lack of excerpts from the original Chinese texts affects the correctness of some interpretations in the reviewed article. Nonetheless, through a dialogue between the two authors and contemporary philosophers, the reviewed article touches upon many philosophical ideas and research topics that are worth reading and studying, especially in terms of socialist philosophy, the historical development of Marxism, and the study of Ukrainian philosophy.